Bibliotherapy Using Picture Books in Improving Knowledge of Clean and Healthy Living Behaviours Among Lower-Year Primary School Children - Putri Aprillia Brilliant Pratama; Rifzul Maulina; Sulistiyah Sulistiyah (Sarana Ilmu Indonesia (Salnesia), 2026)
Clean and Healthy Living Behavior (Perilaku Hidup Bersih dan Sehat/PHBS) is an important effort to improve children’s health status from an early age. However, PHBS implementation in Indonesia remains low. Only 39.1% of households comprehensively practice PHBS, while handwashing with soap reaches only 27.2%. In schools, around 29% of elementary schools lack adequate handwashing facilities, and 18% do not have separate toilet facilities. These conditions contribute to diseases among children, including diarrhea, skin infections, and Acute Respiratory Infections (ARI). The limited effectiveness of conventional learning methods indicates the need for more engaging health education strategies, such as bibliotherapy using illustrated storybooks. This study aimed to analyze differences in PHBS knowledge levels before and after bibliotherapy intervention among lower-grade elementary school students. A quantitative pre-experimental one group pretest–posttest design was used. The sample consisted of 30 third-grade students at MI Sunan Gunung Jati Malang selected through total sampling. Data were collected using a PHBS knowledge questionnaire before and after three bibliotherapy sessions using illustrated storybooks. Data were analyzed using the Wilcoxon test with a significance level of p<0.05. The results showed an increase in the average knowledge score from 1.83 to 2.13. Students with good knowledge increased from 20.0% to 36.7%, while those with low knowledge decreased from 36.7% to 23.3%. The Wilcoxon test showed p=0.020, indicating a significant difference before and after intervention. Bibliotherapy using illustrated storybooks demonstrated an increase in PHBS knowledge and has the potential to serve as an alternative health education strategy in primary schools.